Курганний могильник скіфського часу «Дергачі» - Пеляшенко, К.Ю. (Археологія і давня історія України, 2020)
Публікація присвячена результатам розкопок
курганного могильника скіфського часу біля міста
Дергачі в Харківській області. Подано повну характеристику розкопаних курганів, проаналізовано
поховальний обряд. ﻿The kurgan mound is located on the edge of the right root bank of the river. Lopan (basin of the Seversky Donets river), near the Dergachi city, Kharkiv region. Now the barrow ground has 32 mounds, although at the beginning of the twentieth century had 60—70 kurgans. The first excavations of the cemetery were carried out in 1903 E. P. Trefiliev who had exca
vated 10 mounds. The collection of artifacts has not
survived up today, and the publication of the results contains brief generalizing characteristics of the burial assemblages. For a long time the exact location of the kurgan burial was unknown, and only recently, during the archaeological exploration, the archaeological site was localized. In 2018—2019 the excavations of the site
was resumed. 7 burial mounds were discovered where 6
graves of the Scythian Age were revealed. Burials were not discovered under two mounds, and two one-time burials were found under the one barrow. The obtained
data make it possible to reconstruct the funeral rite. Burials were carried out under mounds of small diam
eter and height. Among the designs of the burial chamber stand out: soil pits, wooden crypts in pits, a pit with shoulders. All burial chambers are directed along the southwest — northeast line, and those buried in them are lied supine, with their heads to the southwest. The grave goods are rather poor, partly due to the robbery of almost all graves. Among the discovered artifacts are the weapons (arrowheads, spear / dart details), jewelry (beads, earrings), household items (knives, awls). A set of signs of the funeral rite suggests that this site is the tribal burial ground of the population who lived in the region at the late 5th—4th centuries BC.